Research into three‐component biodiesel fuels combustion process using a single droplet technique - Raslavičius, Laurencas; Markšaitis, Donatas (Transport, 2007)
In order to reduce the engine emission while at same time improving engine efficiency, it is very important to clarify the combustion mechanism. Even if, there are many researches into investigating the mechanism of engine combustion, so that to clarify the relationship between complicated phenomena, it is very difficult to investigate due to the complicated process of both physical and chemical reaction from the start of fuel injection to the end of combustion event. The numerical simulations are based on a detailed vaporization model and detailed chemical kinetics. The influence of different physical parameters like droplet temperature, gas phase temperature, ambient gas pressure and droplet burning velocity on the ignition delay process is investigated using fuel droplet combustion stand. Experimental results about their influence on ignition delay time were presented.First Published Online: 27 Oct 2010